Analysis of the Sales Budget for Honda and Yamaha Motorcycles in Indonesia in 2023 - Muldiansyah, Muldiansyah; Mulyadi, Adi; Mulyadi, Dani (Maksi, 2024)
This study aims to explore the competitive dynamics in motorcycle sales between Honda and Yamaha in Indonesia throughout 2023. Motorcycle sales in Indonesia exhibit a fascinating rivalry between these two leading brands. Sales data from January to October 2023 reveal that Honda continues to dominate the market with a commanding 78.7% market share, while Yamaha holds the second position with a 20.4% share. This research will analyze the factors contributing to this competition, including the business strategies employed by both brands, the rapid advancements in technological innovation, and the evolving consumer preferences. These aspects are expected to provide deeper insights into the trends and challenges faced by the motorcycle industry in Indonesia. The findings from this study are anticipated to serve as a valuable reference for stakeholders in formulating more effective strategies to navigate the competitive landscape of the automotive market.